EVALUASI PENGEMBANGAN SUMBER DAYA MANUSIA: SEBUAH REVIEW - Titik Nurbiyati (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2015)
Human resource management (HRM) is a recognition of the importance of human labor as vital resources that contribute to the goals of the organization, and utilization of multiple functions and activities to ensure that they are used effectively and fairly for the benefit of individuals, organizations, and society. Now human resource management has a unique and timely opportunity to improve productivity. Eventhough, productivity improvement does not means only increase the output. In addition, the evaluation of program responsibles and meets the special needs of employees with efficient cost. It is a very effective manner that very important, as organizations are tempted to cut costs and improve quality in their company. Without evaluation, it is very difficult to demonstrate that the development is the reason for the improvement. Human Resources Development can maintain and support productivity, as well as company isolate of lack of expertise of the human resources for the current job and future. The results are used in evaluating development programs include participant satisfaction with the training and development program development, learning knowledge or skills, the use of knowledge and skills on the job, and the results such as sale, productivity, or the prevention of accidents. Evaluation can also compare costs against benefits that receive development (return on investment).